The dynamics of Guanxi in the business context under China's economic transition - Nie, Katherine Su (Curtin University, 2007)
Numerous popular business publications and academic literature have highlighted that the Chinese cultural phenomenon of guanxi has made noticeable impacts on the economic efficiency in China’s economic transition. Despite the pervasive belief of the significance of guanxi for facilitating Chinese business transaction, few empirical efforts have been dedicated to comprehensively investigate the dynamics of guanxi in the mainland Chinese business context. Specifically, there is a dearth of empirical evidence to support the anecdotal claims that the guanxi construct and the business strategy orientations are strategically collaborated with the vertical and the horizontal guanxi network, and these operations are influenced by the attributes of organizations and individuals. Consequently, the purpose of this research was to investigate the interactions between the guanxi construct and the business strategy orientation with the vertical and the horizontal guanxi network, as well as the moderating effects that the organizational properties and individual attributes have on the posited interactions.A cross cultural study was conducted in six large coastal and inland cities of Guangzhou, Foshan, Xiamen, Kunming, Hefei and Dalian of mainland China. These six research cities are located in the five large provinces of Guangdong, Fujian, Yunnan, Anhui and Liaoning, which are geographically dispersed from southeastern, southwestern, northeastern to southern China. The six research cities, which were purposely selected across the ‘early’ to ‘late’ open economic regions, are the major centers of the five provinces that have embarked on a modernization policy and market liberalization of the Chinese economy while maintaining traditional values. This study was undertaken with 1033 Chinese business executives who were positioned at the top five senior managerial levels of 480 Chinese organizations across four major industrial fields in the six study cities. The four major industrial fields that were selected in this study were 1) Trading, 2) Building/Construction, 3) Manufacturing, and 4) Service. Although there has been extensive attention on the relevance of guanxi in a relationship based society of China (Gold et al. 2002), few empirical studies that have been conducted in the industrial sectors and across several regional locations that are enmeshed in the revitalization of the Chinese economy. Hence, it is claimed that this study is the first project of its kind that was implemented to empirically investigate the dynamics of guanxi amongst four industrial fields across six cities of mainland China.The study respondents were senior business executives who have overall successful business and managerial careers in directing and developing businesses in mainland China. Many of them have traveled to Western countries frequently, and they possess extensive experience and proven records in global business dealings. More than half of the business executives had at least five years experience in their current industrial fields while nearly half had no less than five years experience in senior managerial levels. One third of the study organizations had existed for five to 10 years, while more than 30 percent of the study organizations had a longer history of more than ten years. And almost one third of the study organizations employed 100 to 500 people, while nearly 20 percent of the organizations have cadres of more than 500 employees. All of the study business executives completed a complex questionnaire for examining a model of the dynamics of guanxi in the business context. The questionnaire was comprised a total of 83 items. Demographic information was sought from the first 12 items of the questionnaire, and a further 72 items that were comprised in three interval instruments that were used to capture the perceptual data of the study.The three interval instruments that were employed in this study included the guanxi construct, the business strategy orientation, and the guanxi network. The instrument of the guanxi construct was developed by two of the guanxi leading scholars (Wong & Leung 2001), and the scale of the guanxi network was developed by several well known guanxi researchers (Davies, Leung, Luk & Wong 1995). These instruments were deliberately chosen because they have shown acceptable psychometric properties (i.e. validity and reliability) in similar assessments, and thus, they were considered appropriated to be adapted and modified for the present study. The modification of these two instruments were undertaken after a systematically study of numerous leading publications pertaining Chinese culture and Chinese Values (e.g., Hofstede 1988; Redding 1990; Luo 2000; Seng & Lim 2004; Xin & Pearce 1996), and thorough consultations with several Chinese Professors of Economics as well as some prominent business people in mainland China. The instrument, which was employed to assess the business strategy orientation in this study, was developed by the researcher. This approach was carried out after a careful study of reputable academic journals and relevant literature (e.g., Aaker 1992; Barnett & Wilsted 1988; Digman 1986; Miles & Snow 1978; Porter 1980; 1985; Pearce & Robinson 1991; Rajagopalan 1997). The development of the instrument involved two separate empirical studies engaging 314 indigenous Chinese managers, who were exclusive of the 1033 study business executives of the main study, in a number of industrial domains in seven large cities of mainland China. In general, the inaugural established instrument of the business strategy orientation and the two adapted scales of guanxi construct and guanxi network were found to have acceptable internal consistencies.A comprehensive pluralist methodology was applied to evaluate the hypotheses of this study. Relevant literature pertaining to the examined variables was reviewed. In light of the literature review, a number of hypotheses and a conceptual model were developed. A quantitative methodology was employed to assess the postulations and qualitative methodology was sought to provide explanations and clarifications of the results. This pluralist methodology is gaining currency in contemporary cross country research. A number of commentators (De Ruyter Moorman & Lemmink 2001; Pearson & Entrekin 1998; Zotteri & Verganti 2001) have contended that a richer and more trustworthy result is likely to be gained by simultaneously pursuing both a quantitative and a qualitative methodology. In total of 1313 questionnaires, which were administrated for completion over six weeks, a total of 1071 questionnaires were returned. However, 38 questionnaires were discarded due to incomplete information provided. The remaining 1033 useful questionnaires generated an overall response rate of 78.67 percent for the six research cities. Comparatively, the response rate of this survey is considerably higher than most of the earlier studies in guanxi research area. More importantly, the high response rate avoids the non response bias in results.Several statistical analyses were employed to evaluate the data. For instance, exploratory factor analysis and reliability analysis were used to assess the psychometric properties of the instruments. The results of psychometric assessments indicated that the scales had good validities and reliabilities, which had potential for robust results. In addition, correlation analysis was applied to evaluate the hypothesized bivariate correlations of the conceptual model. Path analysis was then utilized to test the hypotheses, which were postulated in Chapter Two. The results of path analysis demonstrated that certain facets of the guanxi construct had strong influence on the application of both of the vertical and the horizontal network, whereas particular business strategic approaches had intense interactions with the vertical and the horizontal guanxi network. Moreover, regression analysis was applied to further examine the hypothesized relationships of the conceptual model. The results of the regress analysis illustrated a substantial convergence with the results of path analysis. Furthermore, hierarchical multiple regression analysis was undertaken to determine the moderating effects that the organizational properties and personal attributes have on the hypothesized interactions between the guanxi construct and the business strategy orientation and the vertical and the horizontal guanxi network. The results of these analyses indicated that the attributes of organization and individual played significant moderating roles on a number of the tested correlations. Lastly, the analyses of T-test and ANOVA were employed to evaluate the extent of difference in the demographic elements and structure properties.The results of these tests depicted that there was a considerable degree of consensus for all the tested variables of the study model across the demographic elements and structure properties. A salient feature of this study is the application of qualitative analysis to enhance the understanding of quantitative results. The researcher visited each of the six researched cities again to conduct focus group meetings, which were mainly held in the languages of Mandarin and Cantonese. Most of the meetings were approximately 90 to 120 minutes in duration. Focus group meetings that were conducted in the cities of Kunming, Foshan, Xiamen, Hefei and Dalian were videotaped and subsequently replicated into DVD plates, whilst feedback sections that were carried out in Guangzhou were completed recorded by written notes. A total of 90 business executives participated in 20 focus group meetings, which were recorded in Chinese and accredited English translations were subsequently arranged. The Chinese meeting record contains almost 160,000 words in 240 pages, and the English translation had 248 pages with approximately 100,000 words. General details of the focus group meetings are reported in Chapter Four.The subjects that were discussed in the qualitative feedback sessions mainly encompassed six aspects. First, respondents’ comprehension of the instruments and the suitability of the scales employed in this study were discussed. Second, the results of factor and reliability analyses, particularly relating to some certain emerged patterns and the dimensionalities of instruments were elucidated. Third, extensive comments about the empirical findings in relation to the correlations that were predicted in the studied model and the unexpected relationships were sought, and clarifications to the phenomena caused were also documented. Fourth, the outputs of the analyses of T-test, ANOVA, path analysis, and regression for descriptive statistic and correlation were discussed. Finally, opinions on the discovery of the moderating effects that the moderating variables had on the tested relationships were attained and elucidation to the results were clarified. In general, the qualitative analytical results have broadly enriched the comprehension to the quantitative findings. With extensive reference to the contribution of the 90 business executives in the qualitative analytical sections, a lengthy discussion of the results of the study is elucidated. Following the discussion of results, an outline of the key findings of this research is presented in Chapter Five.A number of theoretical and practical contributions have constructed in this study. The first theoretical contribution of this study is an advancement of the currently available knowledge relating to the operations amongst the guanxi construct with the vertical and the horizontal guanxi network, as well as the interactions between the business strategy orientation with the vertical and the horizontal guanxi network in the business context. A second theoretical contribution of the study is to evaluate Western based theoretical notions in a non Western context. Next, evaluation of the study model has the potential to make further theoretical contribution in terms of enhancing the understanding of Multi National Companies (MNCs) and overseas investors on the imperativeness of the cultural phenomenon of guanxi. The first practical contribution is the investigation of the moderating effects that the attributes of organizations and individuals have on the relationships between the guanxi construct and the business strategy orientation with the vertical and the horizontal guanxi network has significant potential to make contribution to international management in an Asian context. Moreover, the inaugural developed seven point Likert scale instrument for assessing the business strategy orientation in the Chinese business organization is likely to facilitate practical contribution to the development of an universal scale. A further practical contribution is to provide a greater comprehensive insight of the dynamics of guanxi in the business context, which would be beneficial to overseas investors and MNCs when they explore their possible Chinese business ventures. Implications of the findings for business practitioners and the theory developments are comprehensively documented in Chapter Six.This research has merged two salient concluding observations. Firstly, it highlighted the importance of the application of a pluralist methodology in implementing cross cultural studies. The findings of this study suggested that the qualitative investigation technique is essential to capture information that was not attainable through the quantitative assessments and that the qualitative dimension complements the quantitative results. In addition, an extended remark in relation to sampling method was offered for further research in mainland China. Preferably, the guanxi ideology is more practical than the Western traditional ‘mail out’ system when conducting a comprehensive survey in China. Especially, guanxi plays a significant role in attaining genuine and liberated comments for qualitative analysis. Secondly, the results of this study suggested that the global environment has reshaped the quality and mindset of Chinese people and this has resulted in the substantial consensus in conceptualizing the theories of the present study. The salient observations and suggestions for future research are discussed in Chapter Six.